2015
DOI: 10.1021/acscatal.5b00221
|View full text |Cite
|
Sign up to set email alerts
|

Surface Oxidation of Stainless Steel: Oxygen Evolution Electrocatalysts with High Catalytic Activity

Abstract: The cheap stainless commodity steel AISI 304, which basically consists of Fe, Ni, and Cr, was surface-oxidized by exposure to Cl2 gas. This treatment turned AISI 304 steel into an efficient electrocatalyst for water splitting at pH 7 and pH 13. The overpotential of the anodic oxygen evolution reaction (OER), which typically limits the efficiency of the overall water-splitting process, could be reduced to 260 mV at 1.5 mA/cm2 in 0.1 M KOH. At pH 7, overpotentials of 500–550 mV at current densities of 0.65 mA/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
145
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 48 publications
12
145
3
Order By: Relevance
“…As expected, a similar outcome can be derived from the corresponding Tafel lines of samples Co-300 and Ir/Ru, showing a horizontal shift of around 220 mV (Figure 3b). This represents enormous progress, taking into consideration that our group had significant problems with substantially improving the OER properties of steel upon surface oxidation to a level that makes it competitive to IrO 2 -RuO 2 regarding water-splitting properties under neutral conditions 25,45 . Interestingly, at current densities < 5mA/cm 2 the Tafel line belonging to sample Co-300 was substantially stiffer (slope 140.8 mV dec -1 ) than the one assigned to IrO 2 -RuO 2 (slope 225.8 mV dec -1 ) (Figure 3b).…”
Section: Oer Properties In Neutral Mediummentioning
confidence: 99%
“…As expected, a similar outcome can be derived from the corresponding Tafel lines of samples Co-300 and Ir/Ru, showing a horizontal shift of around 220 mV (Figure 3b). This represents enormous progress, taking into consideration that our group had significant problems with substantially improving the OER properties of steel upon surface oxidation to a level that makes it competitive to IrO 2 -RuO 2 regarding water-splitting properties under neutral conditions 25,45 . Interestingly, at current densities < 5mA/cm 2 the Tafel line belonging to sample Co-300 was substantially stiffer (slope 140.8 mV dec -1 ) than the one assigned to IrO 2 -RuO 2 (slope 225.8 mV dec -1 ) (Figure 3b).…”
Section: Oer Properties In Neutral Mediummentioning
confidence: 99%
“…Pure metals and metal alloys have seldom been proposed as OER electrocatalysts in neutral regimes, [48] and the few studies performed showed that the superior OER properties of Ni-containings teel are to some extent restricted to water splitting in alkaline media. [48] Mild steel, for example, steel S235 (standard carbon manganese steel) is based on the promisingi ngredients of manganese and iron and as such is an interesting candidatef or the decrease of the overpotential caused at the anode during the OER in alkaline andn eutral media.…”
Section: à2mentioning
confidence: 99%
“…Besidese lectrodeposited thin metal-containing films, ar ange of metals and metal alloys that include steel have been investigated andp roposed as catalysts for the electrocatalytic OER mainly in alkaline media. Amongst the most promising candidates is Ni, which has been used commerciallya nd utilized as ac atalyst for anodicw ater splitting, [36][37][38] NiFe films [39] as introduced by Corrigana nd Bendert, [40,41] Fe, [38,42,43] Co, [38] steel, [44][45][46][47][48] and Ni-Co alloys. [49,50] To the besto fo ur knowledge,t he highest activity with steel or iron as ac atalystf or the electrochemically assisted water splitting in an alkaline mediumw as achieved recently by our group [51] with an overpotential of 212 mV at 10 mA cm À2 in 1 m KOH, by Lyons and Doyle with 360 mV overpotentiala t1mA cm À2 in 1 m NaOH [43] and6 00 mV overpotential at 10 mA cm À2 in 0.1 m NaOH, [46] and by Moureaux et al with 320 mV overpotential at 10 mA cm À2 in 1 m KOH.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine oxidized AISI 304 steel (Cr-Ni stainless steel) was found to be a mediocre OER electrocatalyst requiring 500 mV overpotential to ensure 0.65 mA cm -2 current density in pH 7 corrected 0.1 M K 2 HPO 4 /KH 2 PO 4 solution [23] . Generally the determined overpotentials for OER on recently developed materials in pH 7 media are relatively close to 500 mV at 1 mA cm -2 current density [30] .…”
Section: Introductionmentioning
confidence: 99%